The neuropeptide tyrosine Y1R is expressed in interneurons and projection neurons in the dorsal horn and area X of the rat spinal cord - Brumovsky, Pablo Rodolfo (2006)
The localization of the neuropeptide tyrosine Y1 receptor was studied with immunohistochemistry in parasagittal and transverse, free-floating sections of the rat lumbar spinal cord. At least seven distinct Y1 receptor-positive populations could tentatively be recognized: Type 1) abundant small, fusiform Y1 receptor-positive neurons in laminae I-II, producing a profuse neuropil; Type 2) Y1 receptor-positive projection neurons in lamina I; Type 3) small Y1 receptor-positive neurons in lamina III, similar to Type 1 neurons, but less densely packed; Type 4) a number of large, multipolar Y1 receptor-positive neurons in the border area between laminae III-IV, with dendrites projecting toward laminae I-II; Type 5) a considerable number of large, multipolar Y1 receptor-positive neurons in laminae V-VI; Type 6) many large Y1 receptor-positive neurons around the central canal (area X); and Type 7) a small number of large Y1 receptor-positive neurons in the medial aspect of the ventral horns (lamina VIII). Many of the neurons present in laminae V-VI and area X produce craniocaudal processes extending for several hundred micrometers. Retrograde tracing using cholera toxin B subunit injected at the 9th thoracic spinal cord level shows that several Type 5 neurons in laminae V-VI, and at least a few Type 2 in lamina I and Type 6 in area X have projections extending to the lower segments of the thoracic spinal cord (and perhaps to supraspinal levels). The present results define distinct subpopulations of neuropeptide tyrosine-sensitive neurons, localized in superficial and deep layers of the dorsal, in the ventral horns and in area X. The lamina II neurons express somatostatin [The neuropeptide Y Y1 receptor is a somatic receptor on dorsal root ganglion neurons and a postsynaptic receptor on somatostatin dorsal horn neurons. Eur J Neurosci 11:2211-2225] and are presumably glutamatergic [Todd AJ, Hughes DI, Polgar E, Nagy GG, Mackie M, Ottersen OP, Maxwell DJ (2003) The expression of vesicular glutamate transporters VGLUT1 and VGLUT2 in neurochemically defined axonal populations in the rat spinal cord with emphasis on the dorsal horn. Eur J Neurosci 17:13-27], that is they are excitatory interneurons under a Y1 receptor-mediated inhibitory influence. The remaining Y1 receptor-positive spinal neurons need to be phenotyped, for example if the large Y1 receptor-positive laminae III-IV neurons (Type 5) are identical to the neurokinin (NK)1R-positive neurons previously shown to receive neuropeptide tyrosine positive dendritic contacts [Polgár E, Shehab SA, Watt C, Todd AJ (1999) GABAergic neurons that contain neuropeptide Y selectively target cells with the NK1 receptor in laminae III and IV of the rat spinal cord. J Neurosci 19:2637-2646]. If so, neuropeptide tyrosine could have an antinociceptive action not only via Y1 receptor-positive interneurons (Type 1) but also projection neurons. The present results show neuropeptide tyrosine-sensitive neuron populations virtually in all parts of the lumbar spinal cord, suggesting a role for neuropeptide tyrosine signaling in many spinal functions, including pain.